Mewujudkan Masyarakat Qur’ani melalui Program KKN STIBA Makassar di Desa Kalabbirang Kabupaten Maros - Sartini Lambajo; Akhmad Hanafi Dain Yunta (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The community service program is a form of the tri dharma of higher education that can be carried out through Student Community Service activities. One of the villages that is the location for the implementation of the STIBA Makassar KKN is Kalabbirang Village, which is located in Bantimurung District, Maros Regency, South Sulawesi. This article aims to provide a description of the community service process carried out by STIBA Makassar students in Kalabbirang Village. The program activities carried out are 1) Friday blessing; 2) Muslim fiqh taklim; 3) TPA development; 4) Dirose program; 5) Tahsin program; 6) Tarbiyah Islamiyah; 7) Halaqoh luhgawiyah; 8) youth taklim; 9) youth taklim; 10) Natural Tadabbur; 11) Handicraft training; 12) Training on organizing the body; 13) Festival of pious children. The results of the community service program contributed greatly to the formation of the Q'uranic community for the people in Kalabbirang Village.